Clinical specialty training in UK undergraduate medical schools: a retrospective observational study. Issue 7 (17th July 2019) - Vaidya, Hrisheekesh J; Emery, Alexander W; Alexander, Emma C; McDonnell, Angus J; Burford, Charlotte; Bulsara, Max K
Abstract : Objectives: To determine if increased exposure to clinical specialties at medical school is associated with increased interest in pursuing that specialty as a career after foundation training. Design: A retrospective observational study. Setting: 31 UK medical schools were asked how much time students spend in each of the clinical specialties. We excluded two schools that were solely Graduate Entry, and two schools were excluded for insufficient information. Main outcome measures: Time spent on clinical placement from UK undergraduate medical schools, and the training destinations of graduates from each school. A general linear model was used to analyse the relationship between the number of weeks spent in a specialty at medical school and the percentage of graduates from that medical school entering each of the Core Training (CT1)/Specialty Training (ST1) specialties directly after Foundation Year 2 (FY2). Results: Students spend a median of 85 weeks in clinical training. This includes a median of 28 weeks on medical firms, 15 weeks in surgical firms, and 8 weeks in general practice (GP). In general, the number of training posts available in a specialty was proportionate to the number of weeks spent in medical school, with some notable exceptions including GP. Importantly, we found that the number of weeks spent in a specialty at medical school did not predict the percentage of graduates of that school training in that specialty at CT1/ST1 level (ß coefficient=0.061, p=0.228). Conclusions: This study found that there was no correlation between the percentage of FY2 doctors appointed directly to a CT1/ST1 specialty and the length of time that they would have spent in those specialties at medical school. This suggests that curriculum adjustments focusing solely on length of time spent in a specialty in medical school would be unlikely to solve recruitment gaps in individual specialties.